Structural, magnetic and electrochemical properties of Al-substituted Ni ferrites for energy storage devices. (1st November 2022) - Hassan, Shahid; Ahmad, Mukhtar; Rehman, Atiq ur; Iqbal, Muhammad Waqas; Shaukat, Saleem Farooq; Abd-Rabboh, Hisham S.M.
Abstract: Ferrite material can be promising materials to solve the global energy crisis and high energy density storage devices. For this, hydrothermally prepared Al substituted Ni ferrites (NiAlx Fe2-x O4, x = 0.0, 0.1, 0.2) have been investigated. To study the effect of substitution of Al on Ni ferrite's structural, magnetic and electrical properties. X-ray diffraction, scanning electron microscopy, Energy dispersive spectrum, Fourier transforms Infrared spectroscopy (FTIR), Vibrating sample magnetometer (VSM), Two Probe technique and cyclic voltammetry (CV) was used to characterize the samples. A single-phase spinel structure was confirmed by XRD diffraction, and the lattice parameter was reduced from 8.40 Å to 8.25 Å. SEM micrographs showed nanoparticles are agglomerated and are non-uniform in size. EDX analysis confirmed that substitution had been successfully achieved. The FTIR spectrum revealed that the absorption band of the octahedral site is around 650 cm −1 for pure Ni ferrite, and this band shifted toward higher frequency with increasing the Al content because substitution of Al reduces the bond length. The M-H loops justified that substitution of nonmagnetic Al (0μB ) decreased the Saturation magnetization (Ms) and increased the Coercivity (Hc). The substitution of Al increased the Ni ferrites' resistivity, making the material suitable for high frequency applications and where low eddy current losses are desirable. CV measurements of the given ferrites show better specific capacitance at a low scan rate. The maximum capacitance has been found to be 42 F/g for x = 0.1 and at a scan rate of 5 mV. The prepared materials can be suitable energy storage devices like supercapacitors. Highlights: Synthesis of Al 3+ substituted Ni spinel ferrites. Lattice constant decreases with Al 3+ substitution and comprehensively alters other structural parameters. Saturation magnetization decreases and magnetic coercivity increases with La +3 substitution. DC electrical resistivity increases with Al 3+ substitution suitable for low eddy current losses. CV measurements show good electrochemical behavior of the prepared ferrites